The Effect of Artificial Intelligence on Learning Outcomes through Students’ Self-Efficacy: A Study of Office Management and Business Services Program Students - Nilam Dela Ardiatna Syafitri; Triesninda Pahlevi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
The use of Artificial Intelligence (AI) in education is increasing; however, empirical evidence on its relationship with learning outcomes through internal psychological mechanisms, particularly self-efficacy in vocational education, remains limited. This study aims to examine the effect of AI usage on students’ learning outcomes, both directly and indirectly through self-efficacy. An explanatory quantitative approach was employed involving 108 students from the Office Management and Business Services program at SMKN 2 Buduran, selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and report card documentation and analyzed using SEM-PLS. The results indicate that AI usage has a positive and significant effect on both learning outcomes and self-efficacy. Self-efficacy also significantly influences learning outcomes and mediates the relationship between AI usage and learning outcomes. These findings highlight the importance of integrating AI not only to enhance information access but also to strengthen students’ psychological aspects.